Cross-age effects on forensic face construction - Fodarella, Cristina; Brown, Charity; Lewis, Amy; Frowd, Charlie D. (Frontiers in Psychology, 2015)
The own-age bias (OAB) refers to recognition memory being more accurate for people of our own-age than other-age groups (e.g., Wright and Stroud, 2002). This paper investigated whether the OAB effect is present during construction of human faces (also known as facial composites, often for forensic/police use). In doing so, it adds to our understanding of factors influencing both facial memory across the life span as well as performance of facial composites. Participant-witnesses were grouped into younger(19-35) and older(51-80) adults, and each constructed a single composite from memory of an own- or cross-age target face using the feature-based composite system PRO-fit. They also completed the 40-item Glasgow Face Matching Test (GFMT; Burton, White and McNeill, 2010). A separate group of participants who were familiar with the relevant identities attempted to name the resulting composites. Correct naming of the composites revealed the presence of an OAB for older adults, who constructed more-identifiable composites of own-age than cross-age faces. For younger adults, age of target face did not influence correct naming and their composites we named at the same level as those constructed by older adults for younger targets. Also, there was no reliable correlation between face perception ability and composite construction.